Analysing the Relationship Between Masculinity and Addiction in terms of Sociological Perspective - Şeyma Yıldırım Yılmaz; Tuğba Aydın Öztürk (İstanbul Üniversitesi Kadın Araştırmaları Dergisi)
This study indicates a relationship between masculinity and substance addiction in relation to gender and that a reason men become addicted to substances is their masculinity crisis. This study aims to highlight this overlooked relationship. The research is significant in terms of providing the opportunity to consider masculinity from a different perspective without emphasising existing masculinity stereotypes, and this subject has not been studied in the literature. To collect the research data, men who had previously or were still diagnosed with substance addiction were interviewed using the in-depth interview technique. After interviews conducted with 10 participants from different age groups, education levels, lifestyles and who underwent substance abuse treatment, a relationship was found between masculinity and substance addiction in relation to gender. The unemployment they experienced, their inability to fulfil their responsibilities, their experience of an event that damaged their masculinity, or the fact that they did not feel sufficiently male were effective in the initiation of substance use by the interviewees. In addition, the interviewees appeared to continue to use substances because the substance made them feel physically and emotionally strong, offered the opportunity to escape from problems, or made them sexually active.